Neutron, proton and electron radiation resistant phase change heat storage integrated structure and preparation method thereof
By designing an integrated phase-change heat storage structure that resists neutrons, protons and electron radiation in the spacecraft, and using lattice to enhance the cavity structure and multifunctional phase-change working fluid, the problem of difficulty in achieving radiation protection and phase-change heat storage in the existing technology is solved, and multifunctional protection and thermal control of sensitive single-aircraft internal aircraft is realized, which improves the reliability and life of the spacecraft.
Patent Information
- Application Number
- CN202411861726.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to achieve neutron, proton, electron radiation protection and phase change heat storage functions in spacecraft at the same time, and common protection methods have problems such as large weight, low protection efficiency, poor designability and single function.
A phase-change heat storage integrated structure that resists neutrons, protons and electron radiation is designed, and a lattice reinforced cavity structure and multifunctional phase-change working fluid are used to enhance the cavity structure and multifunctional phase-change working fluid. The three-dimensional lattice structure and multi-layer metal structure are used to achieve load-bearing, thermal conductivity and radiation protection, and the internal charge of multifunctional phase-change working fluid is used to achieve heat storage and thermal control.
It realizes effective protection of neutrons, protons and electron radiation by sensitive single-machine internal aircraft, and at the same time, constant temperature thermal control is achieved through phase change energy storage, which improves the reliability and life of the spacecraft's on-orbit operation and meets the needs of lightweight multifunctional structures.
Smart Images

Figure CN119637116A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lightweight multifunctional structures of spacecraft, and in particular to a phase change heat storage integrated structure resistant to neutron, proton and electron radiation and a preparation method thereof. Background Art
[0002] As the hub of data processing and transmission, the precision electronic equipment inside the spacecraft is extremely susceptible to the effects of particle radiation. The single particle and total dose effects have become the main causes of spacecraft failures, accounting for about 38% of on-orbit failures. When microelectronic devices are in a radiation environment for a long time, multiple particle radiations will cause charge accumulation in the device, causing the device to deflect from its working state, performance degradation, or even failure. It is necessary to carry out anti-neutron / proton / electron radiation protection design for precision electronic equipment in spacecraft.
[0003] The protection against radiation particles mainly relies on increasing the thickness of mass shielding of spacecraft cabin, protective wall, component packaging, etc., so that aerospace devices receive as little radiation dose as possible. Commonly used shielding methods generally have the disadvantages of heavy weight, low protection efficiency, poor designability, and single function. At the same time, as the temperature environment requirements for the normal operation of precision electronic equipment in spacecraft become more and more stringent, relative constant temperature control can be achieved by absorbing or releasing heat through phase change materials. At present, the research on anti-particle radiation technology for precision electronic equipment in spacecraft mainly includes single-layer / multi-layer metal protection structure, radiation-resistant film / coating composite materials, etc. Patent ZL03115691.6 discloses a method for coating heavy metal materials and polymer binders on the inherent shielding material aluminum or aluminum-magnesium alloy shell of the spacecraft shell to achieve radiation shielding, which can enhance the radiation protection performance of traditional shielding shells. Patent ZL201310021277 discloses a polyethylene composite material doped with carbon nanotubes and nano-tantalum for space charged particle radiation protection and its preparation method and application. Its matrix is polyethylene polymer material, which has poor adaptability to space environment and cannot meet the radiation protection needs of sensitive single-machine satellites with long life. Patent CN202311845583 discloses a satellite structural plate for proton radiation protection in Earth's medium orbit and its manufacturing method, which realizes the integration of structural strength and radiation resistance, but does not have the thermal control function of heat storage and heat expansion. At present, there is no report on an integrated structure that has the ability to protect against neutron, proton, and electron radiation, as well as the phase change energy storage function.
[0004] The present invention designs a multifunctional integrated structure for spacecraft, which protects sensitive units inside the spacecraft and reduces the impact of neutron / proton and electron radiation. At the same time, relatively constant temperature thermal control is performed on the units through phase change energy storage, which can improve the reliability and life of the spacecraft's on-orbit operation. Summary of the invention
[0005] The purpose of the present invention is to address the problems existing in the prior art and the radiation resistance and thermal control requirements of sensitive single-machines inside spacecraft. The present invention provides a phase change heat storage integrated structure resistant to neutron, proton and electron radiation and a preparation method thereof. It has charged particle and neutron radiation protection and thermal control functions based on phase change energy storage, while meeting the requirements for lightweight spacecraft, solving the common shortcomings of commonly used protection means such as heavy weight, low protection efficiency, poor designability, and single function, and has good application prospects in the field of lightweight and multifunctional structures of spacecraft.
[0006] The existing technologies cannot simultaneously possess the functions of phase change heat storage and radiation protection. In the process of improvement, the present invention needs to consider the coordinated design of load-bearing, heat conduction, heat storage, and radiation protection. At the same time, it is necessary to solve the problems of heat exchange between the lattice sandwich structure, the lattice enhanced cavity structure and the phase change heat storage medium, and the dispersion of nanoparticles in the paraffin matrix. The existing technologies have not provided solutions. The phase change heat storage integrated structure resistant to neutron, proton, and electron radiation in the present invention has multiple functions of load-bearing, heat conduction, heat storage, and radiation protection. The coordinated design of the lattice enhanced cavity structure and the multifunctional phase change medium achieves the best comprehensive performance.
[0007] The purpose of the present invention can be achieved by the following scheme:
[0008] The present invention specifically relates to a phase change heat storage integrated structure resistant to neutron, proton and electron radiation, including a lattice enhanced cavity structure and a multifunctional phase change working fluid;
[0009] The lattice enhanced cavity structure includes an external shell, an internal cavity internal support structure translation array;
[0010] The cavity formed by the translation array of the shell and the internal support structure of the cavity is filled with a multifunctional phase change medium;
[0011] The internal support structure of the cavity is a three-dimensional lattice structure, which is composed of comb-shaped fins in oblique and horizontal directions.
[0012] The lattice-enhanced cavity structure of the present invention is a lattice-enhanced sealed interconnected structure. The load-bearing is achieved through three-dimensional lattice enhancement, a heat conduction network is constructed through metal structure interconnection, and a multi-layer metal structure is constructed through lattice configuration regulation to enhance the vertical radiation protection capability. The internal cavity is filled with a multifunctional phase-change medium, and the multi-layer metal structure and the multifunctional phase-change medium simultaneously play a role in blocking charged particles.
[0013] Preferably, the shell is a rectangular cavity structure to form a sealed communication structure. The edges of the inner surface of the shell are chamfered to reduce structural stress concentration.
[0014] Preferably, the oblique comb-shaped fins are preferably two pieces that are crossed and symmetrically arranged.
[0015] Preferably, the comb-shaped fins have comb teeth at both ends, and when the internal support structure of the cavity is viewed from the vertical direction of the shell surface, the comb teeth of the oblique comb-shaped fins cover the comb teeth gaps of the horizontal comb-shaped fins, and the comb teeth of the horizontal comb-shaped fins cover the comb teeth gaps of the oblique comb-shaped fins. The positions of the oblique and horizontal comb-shaped fins are cross-complementary.
[0016] Preferably, the angle between the oblique comb-shaped fins and the horizontal direction is 40-50°, preferably 45°. The oblique and horizontal comb-shaped fins are cross-formed. The comb teeth of the comb-shaped fins diverge outward in six directions, increasing the contact area between the metal structure and the phase change material and improving the heat transfer efficiency. The thickness of the comb-shaped fins is determined according to the strength design.
[0017] Preferably, the width of the comb teeth on the comb-shaped fins is 0.3 mm to 1 mm.
[0018] The width of the comb teeth of the oblique comb-shaped fins is l1;
[0019] The width of the comb teeth gap of the oblique comb-shaped fin is t1;
[0020] The comb teeth width of the comb-shaped fins in the horizontal direction is l2;
[0021] The width of the comb-tooth gap of the comb-shaped fins in the horizontal direction is t2.
[0022] l1=0.3mm~1mm, l2=0.3mm~1mm, and l1≥t2, l2≥t1.
[0023] In the present invention, l1≥t2, l2≥t1, the positions of the comb-shaped fins in the oblique and horizontal directions are cross-complementary, and the comb-shaped fins form a complete protective surface in the horizontal direction, thereby providing maximum protection against charged particles originating from the direction perpendicular to the panel.
[0024] The length of the horizontal comb-shaped fins in the direction of the comb teeth is a, and the height of the oblique comb-shaped fins perpendicular to the shell surface is b.
[0025] The length of the oblique comb-shaped fins perpendicular to the comb teeth is c, and the length of the horizontal comb-shaped fins perpendicular to the comb teeth is c. m l1+m t1=c, n l2+n t2=c, m=n, which is an integer of 4-8, preferably 5.
[0026] The width of the non-comb-toothed portion (the cross-joining portion of different comb-shaped fins) is d, which can be 4 to 10 times the thickness of the fin.
[0027] The lattice-enhanced cavity structure designed in the present invention has a certain load-bearing capacity as a three-dimensional lattice-enhanced sandwich plate structure, which can be used for structures such as a single-machine mounting plate and a single-machine protective cover, and realizes the function of heat storage and heat equalization by filling the internal phase-change heat storage medium. On the other hand, the lattice-enhanced cavity structure shell and the internal lattice structure also play a certain role in radiation protection.
[0028] The three-dimensional lattice is different from the commonly used body-centered cubic, face-centered cubic, pyramid and other configurations. It takes into account the heat exchange between the metal structure and the phase change material, and increases the contact area through the comb-shaped fins in six directions to improve the heat transfer efficiency. At the same time, the fins in the 45° and horizontal directions can achieve load-bearing and thermal conductivity enhancement while the cross-complementary fin positions can maximize the protection of charged particles from the vertical panel direction.
[0029] The shell is provided with a processing filling hole, which is used to fill the multifunctional phase change working medium in the cavity of the lattice enhanced cavity structure.
[0030] Preferably, the overall thickness of the lattice-enhanced cavity structure is 6 to 12 mm. The wall thickness of the shell is 0.5 to 0.8 mm. The lattice-enhanced cavity structure is prepared by laser selective melting forming method, and its material is aluminum alloy or titanium alloy. The chamfer radius of the edge of the inner surface of the shell is 0.3 to 0.5 mm to ensure the quality of laser selective melting forming, while meeting the mechanical properties and lightweight requirements.
[0031] Preferably, the multifunctional phase change working fluid comprises a phase change energy storage working fluid and radiation protection nanoparticles, and the radiation protection nanoparticles comprise metal nanoparticles and non-metallic nanoparticles. The radiation protection nanoparticles are doped into the phase change energy storage working fluid to form a multifunctional phase change working fluid, which has both phase change energy storage and neutron, proton and electron radiation protection capabilities.
[0032] Preferably, the phase change energy storage medium uses paraffin as the base phase change material, with a melting point of 16-30°C. At the same time, paraffin, as a high hydrogen-containing material, has a strong proton blocking ability. (Paraffin is a large category, including n-hexadecane and n-octadecane, etc.)
[0033] Preferably, the metal nanoparticles are heavy metal nanoparticles; the heavy metal nanoparticles include one or more of tantalum, tungsten and titanium nanoparticles.
[0034] Preferably, the non-metallic nanoparticles include carbon nanoparticles and boron nanoparticles.
[0035] The carbon nanoparticles include one or more of carbon nanotubes and graphene.
[0036] The boron nanoparticles include one or more of boron, boron nitride, and boron carbide nanoparticles.
[0037] The metal nanoparticles and non-metal nanoparticles used in the present invention have neutron absorption and electron scattering capabilities. Radiation protection nanoparticles doped in phase change energy storage fluids can simultaneously improve the thermal conductivity of phase change materials and enhance thermal conversion performance (heat equalization capability).
[0038] Different from commonly used polymers, the phase change energy storage medium used in the present invention can solve the problem that the polymer matrix is prone to denaturation and embrittlement under long-term radiation, and also solves the problem of poor thermal conductivity of the polymer matrix material. At the same time, the latent heat characteristics of phase change are utilized to increase the heat storage and heat equalization capabilities.
[0039] Preferably, in the multifunctional phase change working fluid, the mass fraction of metal nanoparticles is 15-24wt%, and the mass fraction of non-metal nanoparticles is 12-20w%. The non-metal nanoparticles are preferably a combination of carbon nanoparticles and boron nanoparticles, with the carbon nanoparticle content being 4-8w%, and the boron nanoparticle content being 8-12w%. The present invention reduces the agglomeration of nanoparticles in liquid paraffin by regulating the content of nanoparticles.
[0040] The present invention also provides a method for preparing the phase change energy storage integrated structure, comprising the following steps:
[0041] Step 1: preparing a lattice-enhanced cavity structure by using a laser selective melting forming method;
[0042] Step 2, preparing a multifunctional phase change working fluid in proportion;
[0043] Step 3: Adjust the ambient temperature to be higher than the melting point temperature according to the melting point of the prepared working fluid;
[0044] Step 4: Fill the liquid working medium into the cavity through the filling hole, and control the filling ratio between 85% and 90%;
[0045] Step 5: heating the filled integrated structure to the highest temperature under the on-orbit use condition until part of the working fluid overflows;
[0046] Step 6: close the filling port and cool to room temperature to obtain the variable energy storage integrated structure.
[0047] Preferably, in step 1, the laser selective melting forming process parameters are set as follows: laser power 250-450w, scanning rate 600-1800mm / s, scanning spacing 100-120μm, layer thickness 30-45μm.
[0048] Preferably, step 2 comprises the following steps:
[0049] Step 2.1: Weigh the mass of the phase change energy storage medium (21) and the radiation protection nanoparticles;
[0050] Step 2.2: Add radiation protection nanoparticles, stir thoroughly under constant temperature heating conditions, and adjust the nanoparticle content several times until there is no obvious agglomeration;
[0051] Step 2.3: Mix evenly to obtain a multifunctional phase change medium (2).
[0052] Preferably, in step 2.2, when the phase change energy storage medium (21) is solid, the phase change energy storage medium (21) is melted and then the radiation protection nanoparticles are added; when the phase change energy storage medium (21) is liquid, the radiation protection nanoparticles are directly added.
[0053] Compared with the prior art, the integrated protection structure of the present invention has the following beneficial effects:
[0054] The integrated protection structure of the present invention is simple and reasonable, with low additional weight and strong feasibility. It can be flexibly applied to the protection structure of sensitive single-unit spacecraft to reduce the damage and destruction of sensitive single-unit spacecraft by particle radiation. Compared with polymer-type radiation protection films, it has stronger tolerance to space environment and service life. At the same time, it has load-bearing and thermal control functions, and can be directly applied to the mounting plate and protective cover of high-power single-unit spacecraft to achieve multi-functional integration, meet the lightweight requirements of spacecraft, and significantly improve the reliability and safety of spacecraft in orbit. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0056] Figure 1 Schematic diagram of the integrated structure of phase change energy storage that is resistant to particle radiation;
[0057] Figure 2 Schematic diagram of the internal support structure of the cavity;
[0058] Figure 3 This is the microscopic morphology of the multifunctional phase change fluid;
[0059] Figure 4 This is a schematic diagram of the proton and electron radiation protection performance test;
[0060] Figure 5 This is a schematic diagram of neutron radiation protection performance test;
[0061] Among them, 1-lattice enhanced cavity structure, 2-multifunctional phase change medium, 11-shell, 12-cavity internal support structure, 13-filling hole, 21-matrix phase change material, 22-metal nanoparticles, 23-non-metal nanoparticles. DETAILED DESCRIPTION
[0062] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
[0063] See also Figures 1 to 3 .
[0064] Example 1
[0065] Example 1 provides an integrated phase change heat storage structure resistant to neutron, proton and electron radiation, which consists of a lattice-enhanced cavity structure and a multifunctional phase change working fluid. The lattice-enhanced cavity structure is a lattice-enhanced sealed and connected structure prepared by a laser selective melting forming method, and the material is aluminum alloy or titanium alloy AlSi10Mg. The outer shell is a rectangular structure with a length of 300mm, a width of 300mm, a thickness of 8mm, and a shell thickness (wall thickness) of 0.5mm. The edges of the inner surface of the shell are chamfered, and the chamfer radius is 0.5mm to reduce stress concentration. The interior of the lattice-enhanced cavity structure is a translation array of the cavity internal support structure. The cavity internal support structure is composed of comb-shaped fins that are inclined at 45° and horizontally, and the structural dimensions are a=b=c=7mm, l1=l2=t1=t2=0.7mm. (The length of the horizontal comb-shaped fins in the direction of the comb teeth is a, and the height of the oblique comb-shaped fins perpendicular to the shell surface is b. The length of the oblique comb-shaped fins perpendicular to the comb teeth and the length of the horizontal comb-shaped fins perpendicular to the comb teeth are c. The width of the comb teeth of the oblique comb-shaped fins is l1; the width of the comb teeth gap of the oblique comb-shaped fins is t1; the width of the comb teeth of the horizontal comb-shaped fins is l2; the width of the comb teeth gap of the horizontal comb-shaped fins is t2)
[0066] The internal cavity of the lattice enhanced cavity structure is filled with a multifunctional phase change medium, which has the functions of bearing, heat transfer and energy storage. The multifunctional phase change medium uses n-hexadecane as the phase change matrix material with a melting point of 18°C, and adds tantalum nanoparticles and carbon nanotubes, wherein the mass fraction of tantalum nanoparticles is 16wt%, the mass fraction of carbon nanotubes is 4wt%, and the mass fraction of boron 10 is 8wt%. On the basis of ensuring the anti-radiation protection ability, the dispersion of doped particles in the phase change matrix material can be improved.
[0067] During the preparation process, the S310 laser selective melting equipment was first used to print the dot matrix enhanced cavity structure. The forming material was AlSi 10Mg alloy powder; considering the density, microstructure and forming efficiency, the process parameters are determined as follows: laser power 350W, scanning rate 1400mm / s, scanning spacing 120μm, layer thickness 30μm. The overall weight of the prepared lattice enhanced cavity structure is 286.9g.
[0068] When preparing the multifunctional phase change working fluid, the materials are calculated and weighed first. Considering the loss during the filling process, 1080g of n-hexadecane, 240g of tantalum nanoparticle powder, 60g of carbon nanotubes, and 120g of boron 10 are weighed respectively. The n-hexadecane is heated to keep it in liquid state, and tantalum nanoparticle powder, carbon nanotubes and boron 10 are added. The mixture is stirred with a constant temperature heated magnetic stirrer for 1 hour until it is mixed evenly. After mixing, it is left to stand for 5 minutes, and there is no obvious particle sedimentation and agglomeration.
[0069] The liquid mixed working fluid is filled into the cavity through the filling hole until the filling volume reaches 82% of the total volume of the cavity. The whole structure is heated to 100°C, and part of the working fluid overflows from the filling port. The filling port is sealed with a plug, and the interface is sealed and welded to ensure the airtightness of the whole structure.
[0070] According to the above scheme, a phase change energy storage integrated structural plate sample resistant to charged particle radiation was manufactured. Its total mass was measured to be 777g, and the average surface density was about 0.86g / cm 2 , the thickness of aluminum alloy or titanium alloy with the same surface density is 3.2mm. Neutron, proton and electron radiation protection performance tests were carried out for the above-mentioned phase change energy storage integrated structural plate resistant to charged particle radiation and aluminum alloy or titanium alloy plate with the same surface density.
[0071] First, the proton protection performance tests were carried out on the integrated structural plate and the aluminum alloy or titanium alloy plate with equal surface area. Figure 4 As shown, a protective plate to be tested is placed at a certain distance from the proton source, and a proton energy detector is placed behind the protective plate, and the proton energy is adjusted to be greater than 30MeV. The proton energy detector is used to record the energy value of the protons after passing through the protective plate to be tested, and finally a transmission energy spectrum is formed. The energy value Ep corresponding to the peak of the transmission energy spectrum (which is also the average energy of the transmitted protons) is selected to characterize the energy of the transmitted protons. The difference between the incident energy and the energy of the transmitted protons is the energy absorbed by the protective plate to be tested; the ratio of the absorbed energy of the integrated structural plate and the aluminum alloy or titanium alloy plate of equal surface area is obtained by calculation, which is the relative proton protection performance multiple.
[0072] Then, the electronic protection performance test is carried out. Figure 4As shown, the protective plate to be tested is placed at a certain distance from the electron source, and the electron energy is adjusted to be greater than 2MeV. The 1# dose sheet is placed in front of the protective plate to be tested to record the absorbed dose D1 without shielding, and the 2# dose sheet is placed behind the protective plate to be tested to record the absorbed dose D2 of the electrons penetrating the sample. The difference is the electron radiation dose absorbed by the protective plate to be tested. The ratio of the absorbed dose of the integrated structural plate and the aluminum alloy or titanium alloy plate of the same surface is obtained by calculation, which is the relative electron protection performance multiple.
[0073] Finally, the neutron protection performance test was carried out. Figure 5 As shown in the figure, a protective plate to be tested is placed at a certain distance from the thermal neutron source. A neutron detector is placed behind the protective plate to be tested, and the neutron flux behind the protective plate is measured; the protective plate is replaced with an aluminum alloy or titanium alloy plate with equal surface density, and the neutron flux after the aluminum alloy or titanium alloy protection is measured; after removing the protective plate, the neutron flux is measured again. The neutron absorption rates of the protective plate and the aluminum alloy or titanium alloy are calculated respectively, and the ratio of the neutron absorption rates of the two is the relative electronic protection performance multiple.
[0074] The test results are as follows:
[0075] (1) With the same surface density (g / cm 2 ) aluminum plate, the proton protection performance of the phase change energy storage integrated structure plate against charged particle radiation is improved by 1.7 times;
[0076] (2) With the same surface density (g / cm 2 ) compared with aluminum plates, the electronic protection performance of the phase change energy storage integrated structural plate that is resistant to charged particle radiation is improved by 1.5 times;
[0077] (3) With the same surface density (g / cm 2 ) compared to aluminum plates, the neutron protection performance of the phase change energy storage integrated structural plate that resists charged particle radiation is improved by 10 times;
[0078] (4) The surface density of the integrated protection structure is 0.86g / cm 2 .
[0079] Example 2
[0080] The lattice-enhanced cavity structure in Example 2 is a lattice-enhanced sealed interconnected structure prepared by laser selective melting forming method, and the material is aluminum alloy or titanium alloy AlSi10Mg. The outer shell is a rectangular structure with a length of 300mm, a width of 300mm, a thickness of 8mm, and a shell thickness of 0.5mm. The edges of the inner surface of the shell are chamfered with a chamfer radius of 0.5mm to reduce stress concentration. The interior of the lattice-enhanced cavity structure is a translation array of the cavity internal support structure. The cavity internal support structure is composed of comb-shaped fins that are inclined at 45° and horizontally, and the structural dimensions are a=b=c=7mm, l1=l2=0.8mm, and t1=t2=0.6mm.
[0081] The multifunctional phase change working fluid uses n-octadecane as the phase change matrix material, with a melting point of 28°C, and adds tantalum nanoparticles and carbon nanotubes, wherein the mass fraction of tantalum nanoparticles is 18wt%, the mass fraction of carbon nanotubes is 6wt%, and the mass fraction of boron 10 is 12wt%. On the basis of ensuring the anti-radiation protection capability, the dispersibility of the doped particles in the phase change matrix material can be improved.
[0082] During the preparation process, the S310 laser selective melting equipment was first used to print the dot matrix enhanced cavity structure. The forming material was AlSi 10 Mg alloy powder; considering the density, microstructure and forming efficiency, the process parameters are determined as follows: laser power 350W, scanning rate 1400mm / s, scanning spacing 120μm, layer thickness 30μm. The overall weight of the prepared lattice enhanced cavity structure is 286.9g.
[0083] When preparing the multifunctional phase change working fluid, the materials are calculated and weighed first. Considering the loss during the filling process, 1130g of n-octadecane, 318g of tantalum nanoparticle powder, 106g of carbon nanotubes and 212g of boron 10 nanometer powder were weighed respectively. The n-octadecane was heated to keep it in liquid state, and the tantalum nanoparticle powder and carbon nanotubes were added. The mixture was stirred with a constant temperature heated magnetic stirrer and stirred for 1 hour until it was evenly mixed. After the mixture was left to stand for 5 minutes, some nanoparticles settled and the carbon nanotubes had slight agglomeration.
[0084] The liquid mixed working fluid is filled into the cavity through the filling hole until the filling volume reaches 82% of the total volume of the cavity. The whole structure is heated to 100°C, and part of the working fluid overflows from the filling port. The filling port is sealed with a plug, and the interface is sealed and welded to ensure the airtightness of the whole structure.
[0085] According to the above scheme, a phase change energy storage integrated structural plate sample resistant to charged particle radiation was manufactured. Its total mass was measured to be 817g, and the average surface density was about 0.91g / cm 2, the thickness of aluminum alloy or titanium alloy with the same surface density is about 3.3mm. For the above-mentioned phase change energy storage integrated structural plate resistant to charged particle radiation and aluminum alloy or titanium alloy plate with the same surface density, proton and electron radiation protection performance tests were carried out respectively, and the test method was referred to Example 1.
[0086] The test results are as follows:
[0087] (1) With the same surface density (g / cm 2 ) aluminum plate, the proton protection performance of the phase change energy storage integrated structure plate against charged particle radiation is improved by 1.8 times;
[0088] (2) With the same surface density (g / cm 2 ) compared with aluminum plates, the electronic protection performance of the phase change energy storage integrated structural plate that is resistant to charged particle radiation is improved by 1.4 times;
[0089] (3) With the same surface density (g / cm 2 ) compared to aluminum plates, the neutron protection performance of the phase change energy storage integrated structural plate that resists charged particle radiation is improved by 10 times;
[0090] (4) The surface density of the integrated protection structure is 0.91g / cm 2 .
[0091] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.
Claims
1. A phase change heat storage integrated structure resistant to neutron, proton and electron radiation, characterized in that: It comprises a lattice-enhanced cavity structure (1) and a multifunctional phase-change working fluid (2); The lattice enhanced cavity structure (1) comprises an external shell (11), an internal cavity internal support structure (12) and a translation array; The cavity formed by the translation array of the shell (11) and the cavity internal support structure (12) is filled with a multifunctional phase change working medium (2); The cavity internal support structure (12) is a three-dimensional lattice structure, which is composed of comb-shaped fins in the oblique and horizontal directions.
2. The phase change heat storage integrated structure according to claim 1, characterized in that: The shell (11) is a rectangular cavity structure, forming a sealed communication structure.
3. The phase change heat storage integrated structure according to claim 1 is characterized in that: The two ends of the comb-shaped fins are comb teeth. When the support structure (12) inside the cavity is viewed from the vertical direction of the shell (11) surface, the comb teeth of the oblique comb-shaped fins cover the gaps between the comb teeth of the horizontal comb-shaped fins, and the comb teeth of the horizontal comb-shaped fins cover the gaps between the comb teeth of the oblique comb-shaped fins.
4. The phase change heat storage integrated structure according to claim 1, characterized in that: The housing (11) is provided with a machined filling hole (13).
5. The phase change heat storage integrated structure according to claim 1, characterized in that: The overall thickness of the lattice-reinforced cavity structure (1) is 6 to 12 mm; and / or, the wall thickness of the housing (11) is 0.5 to 0.8 mm; And / or, the chamfer radius of the edge of the inner surface of the shell (11) is 0.3-0.5 mm.
6. The phase change heat storage integrated structure according to claim 1, characterized in that: The multifunctional phase-change working medium (2) comprises a phase-change energy storage working medium (21) and radiation protection nanoparticles, and the radiation protection nanoparticles comprise metal nanoparticles (22) and non-metal nanoparticles (23).
7. The phase change heat storage integrated structure according to claim 6, characterized in that: The phase-change energy storage medium (21) is paraffin; And / or, the metal nanoparticles (22) are heavy metal nanoparticles; the heavy metal nanoparticles include one or more of tantalum, tungsten, and titanium nanoparticles; And / or, the non-metallic nanoparticles (23) include one or more of carbon nanoparticles and boron nanoparticles; The carbon nanoparticles include one or more of carbon nanotubes and graphene; The boron nanoparticles include one or more of boron, boron nitride, and boron carbide nanoparticles.
8. The phase change heat storage integrated structure according to claim 1, characterized in that: In the multifunctional phase change working fluid (2), the mass fraction of metal nanoparticles is 15-24wt%; the mass fraction of non-metal nanoparticles is 12-20w%.
9. A method for preparing the phase change energy storage integrated structure as claimed in claim 1, characterized in that: The following steps are involved: Step 1: preparing a lattice-enhanced cavity structure by using a laser selective melting forming method; Step 2, preparing a multifunctional phase change working fluid (2) according to a certain proportion; Step 3, adjusting the ambient temperature to be higher than the melting point temperature according to the prepared working fluid melting point; Step 4: Fill the liquid working medium into the cavity through the filling hole, and control the filling ratio between 85% and 90%; Step 5: heating the filled integrated structure to the highest temperature under the on-orbit use condition until part of the working fluid overflows; Step 6: close the filling port and cool to room temperature to obtain the variable energy storage integrated structure.
10. The method for preparing the phase change thermal storage integrated structure according to claim 9, characterized in that: The step 2 comprises the following steps: Step 2.1: The multifunctional phase change working fluid (2) includes a phase change energy storage working fluid (21) and radiation protection nanoparticles, and the masses of the phase change energy storage working fluid (21) and the radiation protection nanoparticles are weighed; Step 2.2: Add radiation protection nanoparticles, stir thoroughly under constant temperature heating conditions, and adjust the nanoparticle content several times until there is no obvious agglomeration; Step 2.3: Mix evenly to obtain a multifunctional phase change medium (2).
Citation Information
Patent Citations
Polyethylene composite material mixed with carbon nano tube and nanometer tantalum and used for space charged particle radiation protection and preparation method and application thereof
CN103093844A
Satellite structure plate for earth middle orbit proton radiation protection and manufacturing method thereof
CN117774360A